Socioeconomic aspects of producers of artisanal sweets in the ‘Baixada Cuiabana’ lowland region of Mato Grosso (Research, Society and Development, 2020)
The production of sweets and similar sugarcane products is an activity performed by smallholder farmers from Acorizal, Cuiabá, Jangada, Nossa Senhora do Livramento, and Santo Antônio do Leverger, in Mato Grosso. Therefore, this study aimed to assess the socioeconomic and productive aspects of rural producers (individuals and/or families) that work with the production of sweets and sugarcane derivatives in municipalities of the ‘Baixada Cuiabana’ region.  145 questionnaires were applied to rural producers in the period from March 2019 to January 2020. Among the main results, it was verified that the predominant profile is of rural producers with a low education level, with properties with a size smaller than a fiscal module (the size varies for each municipality), without DAP possession and/or access to sectorial public policies, such as PRONAF and ATER services. Furthermore, the main income source of the interviewees was the production of sweets and similar sugarcane-derived products, and the financial gain of most individuals was up to a minimum wage. Therefore, it is verified that the low education level and the absence of technical orientation might be conditioning for the permanence of farmers in situations of socioeconomic vulnerability.